Production of Interleukin-8 by Human Neutrophils Stimulated with Trichomonas vaginalis - Ryu, Jae-Sook (American Society for Microbiology, 2004)
Neutrophils are the predominant inflammatory cells found in the vaginal discharges of patients infected with Trichomonas vaginalis. Although chemoattractants, such as leukotriene B(4) and interleukin-8 (IL-8), are found in the vaginal discharges of symptomatic trichomoniasis patients, little is known about the mechanism of how neutrophils accumulate or mediate initial inflammatory response after acute T. vaginalis infection. We examined IL-8 production in neutrophils activated by T. vaginalis and evaluated the factors involved in T. vaginalis adherence that might affect IL-8 production. When human neutrophils were stimulated with live trophozoites, T. vaginalis lysate, or T. vaginalis excretory-secretory products, the live trichomonads induced higher levels of IL-8 production than the lysate or products did. When live trichomonads were pretreated with various inhibitors of proteinase, microtubule, microfilament, or adhesin (which are all known to participate in the adherence of T. vaginalis to vaginal epithelial cells), IL-8 production significantly decreased compared with the untreated controls. Furthermore, an NF-κB inhibitor (pyrrolidine dithiocarbamate), a mitogen-activated protein (MAP) kinase (MEK) inhibitor (PD98059), and a p38 MAP kinase inhibitor (SB203580) significantly suppressed IL-8 synthesis in neutrophils. These results suggest that live T. vaginalis, particularly adherent trophozoites, can induce IL-8 production in neutrophils and that this action may be mediated through the NF-κB and MAP kinase signaling pathways. In other words, T. vaginalis-induced neutrophil recruitment may be mediated via the IL-8 expressed by neutrophils in response to activation by live T. vaginalis.